1994
DOI: 10.1002/ddr.430330405
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect on reduction in blood pressure with coadministration of a renin inhibitor or an angiotensin‐converting enzyme inhibitor with an angiotensin II receptor antagonist

Abstract: The effects of coadministration of a renin inhibitor, terlakiren, and an angiotensinconverting enzyme inhibitor, captopril, with the angiotensin II receptor antagonist, losartan, on blood pressure of sodium-depleted guinea pigs were studied. Dose-response relationships for terlakiren (0.1 to 3.0 mg/kg, iv), captopril (0.03 to 1.0 mgikg, iv), and losartan (0.1 to 6.0 mgikg, iv) were obtained either alone or in the presence of a submaximal dose of the other inhibitor. The hypotensive response calculated for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…However, the clinical significance of this finding remains debatable, in that it was derived mostly from studies with limitations of methodology, such as experimental conditions [5][6][7][8][9][10], evaluation of a normotensive population [11], blood pressure assessment exclusively by office measurements [14,16,17], or use of ACEI or ARB monotherapy at submaximal doses [13,15,17]. Interestingly, it has been suggested that the administration of an ACEI might not provide additional antihypertensive effect if the angiotensin II type 1 (AT 1 ) receptor has been effectively blocked by an ARB [11].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the clinical significance of this finding remains debatable, in that it was derived mostly from studies with limitations of methodology, such as experimental conditions [5][6][7][8][9][10], evaluation of a normotensive population [11], blood pressure assessment exclusively by office measurements [14,16,17], or use of ACEI or ARB monotherapy at submaximal doses [13,15,17]. Interestingly, it has been suggested that the administration of an ACEI might not provide additional antihypertensive effect if the angiotensin II type 1 (AT 1 ) receptor has been effectively blocked by an ARB [11].…”
Section: Introductionmentioning
confidence: 94%
“…Accumulating evidence suggests that the combination of an ACEI with an ARB provides a greater blood pressure-decreasing effect than either drug given as monotherapy [5][6][7][8][9][10][11][12][13][14][15][16][17]. However, the clinical significance of this finding remains debatable, in that it was derived mostly from studies with limitations of methodology, such as experimental conditions [5][6][7][8][9][10], evaluation of a normotensive population [11], blood pressure assessment exclusively by office measurements [14,16,17], or use of ACEI or ARB monotherapy at submaximal doses [13,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…11 (9)(10)(11)(12)(13)(14) b,d valsartan alone. The AUC 0 -24 of plasma active renin concentration for the A150ϩV80 combination was significantly higher than that achieved with 160 mg of valsartan and similar to that achieved by A300 alone.…”
Section: Combined Blockade Of the Ras By Aliskiren And Valsartanmentioning
confidence: 99%
“…Thus, we investigated whether a combination of the orally active potent alkane carboxamide renin inhibitor aliskiren (150 mg) (9,10) and the AT1R antagonist valsartan (80 mg), which inhibit the RAS at the first and last steps, respectively, results in a stronger blockade of the RAS and larger decreases in aldosterone excretion than higher doses of each RAS inhibitor given alone. Synergistic effects of a combination of a renin inhibitor and AT1R blocker on BP have been demonstrated in a preclinical study (11). We have used the same clinical and laboratory methods as those previously used to differentiate the combination of an ACE inhibitor and AT1R antagonist from each component (12,13).…”
mentioning
confidence: 99%
“…Therefore, our current results of greater attenuation of BP with combined therapy of ACE inhibitors with ARBs indicate that multi-step therapeutic intervention more effectively blocks the renin-angiotensin system. This is supported by other trials in which combined therapy of captopril with renin inhibitors such as CP-80,794 (Fossa et al, 1992) or terlakiren (Fossa et al, 1994) also produced a synergistic effect on lowering blood pressure.…”
Section: Discussionmentioning
confidence: 54%